2018
DOI: 10.4155/bio-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Dried Urine Swabs as a Tool for Monitoring Metabolite Excretion

Abstract: Although this technique seems very promising more methodological studies have to be conducted in order to improve applicability of dried urine microvolume fluidic sampling for quantitative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Dried urine has also been used to measure other urine analytes of interest, such as sodium and potassium, with similarly high levels of stability 62 . As with others who used either lter paper or cotton swabs 63 , we found that dried urine results are in agreement with liquid urine results, reduced the burden on patients, and had good stability over time 12 . Still, agreement between 24-h urine collections and early-morning, single spot urine collections for hormonal analysis are often poor 64 .…”
Section: Discussionsupporting
confidence: 88%
“…Dried urine has also been used to measure other urine analytes of interest, such as sodium and potassium, with similarly high levels of stability 62 . As with others who used either lter paper or cotton swabs 63 , we found that dried urine results are in agreement with liquid urine results, reduced the burden on patients, and had good stability over time 12 . Still, agreement between 24-h urine collections and early-morning, single spot urine collections for hormonal analysis are often poor 64 .…”
Section: Discussionsupporting
confidence: 88%
“…The MetAl trial aimed to identify new alcohol biomarkers in blood, urine, and hair [ 83 ] and was without a wash-out period due to the aim of exploring acute changes in intake biomarkers with changes in alcohol intake. Therefore, the study is prone to carry-over effects, and carry-over was observed for one variable, HDL 2a -apoA1.…”
Section: Discussionmentioning
confidence: 99%
“…The first is a white paper coming out of a recent Japan Bioanalysis Forum meeting, detailing outcomes of the discussions concerning the best selection strategy for surrogate matrices as applied to both LC-MS and ligand binding assays [1]. Following this, there is a fascinating comparison of data, obtained by Monošík and Dragsted, using dried urine swab samples against wet urine samples for the quantitative determination by UHPLC-MS of a suitably chemically diverse range of dietary metabolites [2]. Subsequently there is a report of the successful LC-MS/MS method validation by Ferreira et al, using a water-based surrogate matrix, of dexamethasone in human aqueous humor [3].…”
Section: Recent Thinking and Empirical Outcomesmentioning
confidence: 99%